The influence of gender of students on the collection of materials in the libraries of exclusive high schools - Maronilla, Rommel F. (2006)
Libraries are expected to cater to the information needs and interests of the basic clientele that they serve. If these needs and interests are given primary consideration, then the libraries are really able to fulfill their purposes.